Desenvolvimento da escrita: o letramento digital como estratégia de ensino - Andrade, Carolina Santos Melo de (2021)
This research undertakes reflections on the efficiency of methods and practices of teaching writing via digital resources. This study was accomplished through a qualitative action-research, which enabled the production and application of on-line teaching strategies, as a mediating mechanism in the writing teaching-learning process. The purpose of the research was to observe and analyze the strengths and weaknesses of digital teaching strategies in the development of written competence, through the Distance Learning method (EaD), with senior students from public high schools in the city of Quirinópolis-GO. Therefore, two editions of an on-line writing course were offered, developed in the light of the theories of Sociodiscursive Interactionism. As a corpus of our research, the discursive production processes materialized in the hypertext, and the tools of the virtual environment MOODLE (AVA) were used, and the impacts of the applied digital strategies were analyzed. Some Bakhtinian concepts were highlighed, among them, interaction and dialogism, using the theoretical-methodological current of Sociodiscursive Interactionism (ISD), which seeks to reflect on collective social activities and language activities, according to the postulates of Bronckart (2006) and Machado (2005). We were guided by the didactic sequence and the teaching genres perspective in Dolz, Noverraz and Schenewly (2004) and Nascimento (2014) and resorted to referrals from the High School National Curriculum Parameters (PCNEM, 2000), the National Common Curricular Base (BNCC, 2018) and other documents that guide Education, regarding language teaching, subsidized by technological artifacts. We mobilized the concept of multiliteracy and multisemiosis by Rojo e Moura (2012) and reflected on the skills and capacities required to develop the multiple forms of digital literacies, listed and categorized by Dudeney et. al. (2016) and Zacharias (20016). This research aims to contribute towards thinking didactic strategies for teaching writing, making didactic transpositions of digital resources subsidized by virtual learning environments, in order to enhance the development of the discursive writing competence. And also to promote a holistic analysis of the teacher, student, technologies and linguistic-textual-discursive knowledge relation. We recognize the potentialities that interaction through the semioses of multimodal genres is capable of promoting in virtual learning spaces.